A Simple Theory of International Trade with Multinational Corporations - Helpman, Elhanan (Journal of Political Economy, 1984)
Using the idea that firm-specific assets associated with marketing, management, and product-specific R & D can be used to service production plants in countries other than the country in which these inputs are employed, I develop a simple general equilibrium model of international trade in which the location of plants in a differentiated product industry is a decision variable. The model is then used to derive predictions of trade pattern, volumes of trade, the share of intra-industry trade, and the share of intrafirm trade as functions of relative country size and differences in relative factor endowments.